2012
DOI: 10.21236/ada559436
|View full text |Cite
|
Sign up to set email alerts
|

Novel Metal-Matrix Composites With Integrally-Bound Nanoscale Carbon

Abstract: We characterized the chemical, thermophysical, and mechanical properties of nanomaterials with up to 5 wt% nanocarbon (aka "covetics") in aluminum and copper metals. The nanocarbon is detectable by EDS and XPS but not by analytical methods such as LECO and GDMS. Nanocarbon raises the melting point and significantly alters surface tension, and thus porosity, during solidification. Open questions remain about the observation of higher density than would be predicted by the rule of mixtures. In aluminum alloys, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Since pure aluminium is expensive, prone to oxidation and corrosion, and not useful for most industrial applications, studies of widely used commercial aluminium alloy series are useful for practical applications keeping in mind that many body alloy systems often complicate the analysis of the structure and phases. Previously reported mechanical studies of these Al-covetic samples of Al-6061 and Al-7075 have shown remarkable improvements [17]. Namely, the ultimate tensile strength increased by 40% and hardness increased over 30% for 5% C in Al-7075 compared with pure Al-7075 [18].…”
Section: Introductionmentioning
confidence: 97%
“…Since pure aluminium is expensive, prone to oxidation and corrosion, and not useful for most industrial applications, studies of widely used commercial aluminium alloy series are useful for practical applications keeping in mind that many body alloy systems often complicate the analysis of the structure and phases. Previously reported mechanical studies of these Al-covetic samples of Al-6061 and Al-7075 have shown remarkable improvements [17]. Namely, the ultimate tensile strength increased by 40% and hardness increased over 30% for 5% C in Al-7075 compared with pure Al-7075 [18].…”
Section: Introductionmentioning
confidence: 97%
“…It is being reported that those composites have higher electrical and mechanical properties, corrosion resistance, thermal conductivity, and other properties. [7,8,[13][14][15][16][17][18] The inventor of the metallurgical production method of nanocomposite materials called ''Covetic'' is Third Millennium Materials, LLC (Dayton, Ohio). Historically, the incorporation of carbon into metals that are not strong carbide formers (like Al, Cu, Ag, Au, Sn, Zn, and Pb) has been technologically difficult because of low carbon wettability.…”
Section: Introductionmentioning
confidence: 99%
“…The high conductivity of Brown's as-extruded covetic sample needs to be repeated due to likely errors caused by short sample length, larger sample diameter, and the resulting low resistance; the as-extruded sample results were also not consistent with the other conductivity measurements or density results. 7 Forrest et al 8 examined Cu covetic material and found negligible density changes, a 20 °C increase in melting temperature, and premature failure in tension believed to be due to porosity in the centrifugally cast specimen. 8 In work due to Isaacs et al, 9 nominal Cu-4 and 5 wt.% C covetic material was supplied by GDC Industries and then used as target material in evaporation deposition processes to form thin film transparent electrodes.…”
mentioning
confidence: 99%
“…7 Forrest et al 8 examined Cu covetic material and found negligible density changes, a 20 °C increase in melting temperature, and premature failure in tension believed to be due to porosity in the centrifugally cast specimen. 8 In work due to Isaacs et al, 9 nominal Cu-4 and 5 wt.% C covetic material was supplied by GDC Industries and then used as target material in evaporation deposition processes to form thin film transparent electrodes. 9 Photoelectron spectroscopy (XPS) and transmission electron microscopy showed carbon structures in the bulk covetic material, but C could not be detected in the deposited films.…”
mentioning
confidence: 99%